What Does Being an "American" Look Like in the Therapy Room?. (3rd July 2017) - Gupta, Rohini
ABSTRACT: A clinical experience of an Asian Indian therapist working with a client of a similar ethnic background is analyzed. The relational dynamics in the therapy and the impact of a perceived shared identity are examined. Transference and countertransference processes are emphasized. A shared perceived ethnic identity created complexities in the therapeutic relationship and affected the therapy in surprising ways. Assumptions related to a shared ethnic identity affected the ability to form a therapeutic alliance.